Operations strategy in perspective: the means for achieving superior performance - Picasso, Fernando Gonçalves (2014)
Manufacturing strategy has been widely studied and it is increasingly gaining attention. It has a fundamental role that is to translate the business strategy to the operations by developing the capabilities that are needed by the company in order to accomplish the desired performance. More precisely, manufacturing strategy comprises the decisions that managers take during a certain period of time in order to achieve a desire result. These decisions are related to which operational practices and resources are implemented. Our goal was to identify the relationship between these two decisions with operational performance. We based our arguments on the resource-based view for identifying sources of competitive advantage. Hence, we argued that operational practices and resources affect positively the operational performances. Additionally, we proposed that in the presence of some resources the implementation of operational practices would lead to a greater performance. We used previous scales for measuring operational practices and performance, and developed new constructs for resources. The data used is part of the High Performance Manufacturing project and the sample is composed by 291 plants. Through confirmatory factor analysis and multiple regressions we found that operational practices to a certain extant are positively related to operational performance. More specifically, the results show that JIT and customer orientation practices have a positive relationship with quality, delivery, flexibility, and cost performances. Moreover, we found that resources like technology and people explain a great variance of operational performance.